Efficacy of Herbal Medicines on Lung Function in Asthma: a systematic review and meta-analysis of randomized controlled trials - Alireza Derakhshan; Masoumeh Sadeghi; Amir-Mo; Mohsen Dehghani; Roshanak Salari; Majid Khadem-Rezaiyan; Majid Mirsadraee; Shahin Saeidinejat; Shima Jalali; Shabnam Jalali (Korean Pharmacopuncture Institute, 2023)
Objectives: The present study was designed to conduct a comprehensive systematic review and meta-analysis to assess the efficacy of herbal medicines as add-on therapy on lung function in asthmatic patients.Methods: A comprehensive search of online databases was performed up to December 2021 to identify randomized controlled trials that used orally herbal preparations for asthma as add-on therapy. Studies were assessed for methodological quality using the Cochrane Collaboration's Risk of Bias tool. The main outcome was percent predicted value of forced expiratory volume (% predicted FEV1). Pooled weighted mean difference (WMD) estimate with corresponding 95% confidence interval (CI) was calculated using inversevariance weights method while random effects meta-analysis was used, taking into account clinical and conceptual heterogeneity.Results: As a result, 1,525 studies were identified. 169 studies were reviewed in-depth and 23 studies met our systematic review inclusion criteria. Finally, nine randomized controlled trials were included in the meta-analysis. Findings indicated that use of herbal medicines in patients with asthma significantly improved % predicted FEV1 (WMD: 3.73, 95% CI: 1.76-5.70), with no evidence for significant heterogeneity (p = 0.56 [Q statistic], I2 = 0.0%). In subgroup analysis by age, improvement in % predicted FEV1 was higher and significant in adults (WMD: 5.16; 95% CI: 2.68-7.63) compared to children (WMD = 1.27; 95% CI: −1.98-4.51). Sensitivity analysis showed the significant effect of herbal medicine consumption on improving FEV1 was consistently (range of summary WMDs: 3.27-4.59), indicating that the meta-analysis model was robust. There was no evidence of publication bias both visually and statistically.Conclusion: Findings support, the complementary use of herbal medicines resulted in significant improvement in the lung function compared to standard treatment in asthmatic patients with no considerable adverse events. This improvement is more likely to be observed amongst adults.